Vivências e desafios de professoras readaptadas na cidade de Corumbá - Zenaide Valéria Leite Olarte (2023)
This research has the general objective of understanding the experiences of elementary school teachers I, belonging to the Municipal Education Network of Corumbá/MS, readapted from their role due to removal from teaching due to illness and, as specific objectives, to characterize the current municipal policy on the teacher readaptation; identify the experiences of pleasure (sublimation) and pathogenic suffering (illness, malaise and collective strategies) related to the new functions in readaptation, taking into account the organization of work, working conditions and social relations. It's a qualitative and exploratory study, whose theoretical contribution isbased on the theory of Psychodynamics of Work, proposed by Christophe Dejours, which aims to understand the psychic and subjective aspects mobilized from the relations and organization of work, studying the visible and invisible aspects that are developed and established from work situations. Five readapted teachers participated in the research, from January 2018 to December 2020, working in the urban area of Corumbá/MS. To map this study, the following instruments we’re used: the Inventory of Risks and Pathogenic Suffering at Work and semi-structured interviews. The analysis of the interviews was submitted to the Analysis of the Nuclei of Sense (ANS) proposed by Mendes (2007). The results of the research revealed that despite the readaptation being instituted 31 years ago in Corumbá/MS, in the way it has been carried out, instead of easing the suffering of the teachers, this institute manifests a feeling of rejection, insecurity, prejudice and violence in the sick teachers. . The meaning at work comes with recognition and depends on the organization where they are inserted and the activities they develop, as the lack of recognition aggravates the pathogenic condition of these professionals. Therefore, it is necessary to implement public policies that allow a readaptation without prejudice and exclusion, capable of promoting the redefinition of the suffering of the readapted professionals.